PENGEMBANGAN MODUL TERAPI AL-QUR’AN SURAH AL-INSYIRAH AYAT 1-8 UNTUK MENGURANGI RASA CEMAS SISWA SAAT MENGHADAPI UJIAN SEKOLAH DI SMK ABDURRAB PEKANBARU - Ayumi, Monica; Saam, Zulfan; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This study determines to develop a therapy module of Al-Qur'an Surah Al-Insyirah Verses 1-8 to reduce student’s anxiety when facing school exam. The type of this study is Research and Development (R&D) which is limited to a few stages by conducting research but not continuing with field testing. In developing a better module, this research carried out a validation test for two areas of expertise, which are material experts and interpreters. The data collection techniques in this study used study of literature and validation questionnaires. The result of this research is that the compiled module of Al-Qur'an Surah Al-Insyirah Verses 1-8 to reduce student anxiety when facing school exams divided into five guidance activities with a total reading duration of ± 45 minutes. The result of the module validation test as a whole based on the material and interpretation aspects shows that the assessment obtained an average value of 83.29% declared